2016
DOI: 10.3390/en9070562
|View full text |Cite
|
Sign up to set email alerts
|

Energy Management in Prosumer Communities: A Coordinated Approach

Abstract: Abstract:The introduction of uncontrollable renewable energy is having a positive impact on our health, the climate, and the economy, but it is also pushing the limits of the power system. The main reason for this is that, in any power system, the generation and consumption must match each other at all times. Thus, if we want to further introduce uncontrollable generation, we need a large ability to manage the demand. However, the ability to control the power consumption of existing demand management approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 38 publications
0
23
0
1
Order By: Relevance
“…Together with methodologies of engaging the community in microgrid operation and maintenance, a long-run benefit is envisioned [14]. Besides optimal operation techniques for a single home or microgrid, various control strategies have been proposed in the literature that consider several characteristics of the microgrid operation [23,24]. In [25] it is shown that in order to overcome the uncertainty of PV generation, demand response (DR) and battery energy storage systems (BESS) need to be introduced simultaneously in an optimal scheduling algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Together with methodologies of engaging the community in microgrid operation and maintenance, a long-run benefit is envisioned [14]. Besides optimal operation techniques for a single home or microgrid, various control strategies have been proposed in the literature that consider several characteristics of the microgrid operation [23,24]. In [25] it is shown that in order to overcome the uncertainty of PV generation, demand response (DR) and battery energy storage systems (BESS) need to be introduced simultaneously in an optimal scheduling algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…In smart grid, the energy providers can monitor the operating states of the loads in real time and control power supply directly. Demand-side energy management has been a hot topic in recent years [3,4]. Reasonable energy management can effectively promote the development of clean energy, save resources and reduce generation costs.…”
Section: Introductionmentioning
confidence: 99%
“…These trade-offs exist between different stakeholder goals, between risk aversion and productivity, and between satisfying short-or long-term objectives. In power grid one might account for reaching agreements with prosumers [8]. In water management this could mean balancing salt, water and agricultural productivity [7].…”
Section: Resilience Managementmentioning
confidence: 99%